Kooperacja małych przedsiębiorstw handlowych jako warunek konkurencyjności na rynku Unii Europejskiej (na przykładzie województwa podkarpackiego) - Dybka, Sławomir; Kuźniar, Wiesława (Cooperation of Small Trade Enterprises as a Condition of Competitiveness on the Market of the European Union (on the Example of Podkarpackie Voivodship), 2005)
The premise of cooperation development in the sphere of trade is small economic potential of Polish enterprises especially considering increasing competition on the market of united Europe. Trade enterprises can be integrated in a horizontal and vertical system. Cooperating enterprises increase their interaction force within the confines of buying groups, which are the most often appearing areas enabling to obtain the effect scale. Enterprises acting in the Podkarpackie voivodship, as in whole country, still exert low degree of integration, expressed by number of functioning companies within the confines of integrated relationships.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 172-177